Pięć wieków rewolucji demograficznej w Europie Zachodniej - Mols, Roger (Wydział Prawa i Administracji UAM, 1981)
We can simultaneously talk about social and historic advantages resulting from investigation of demographic revolution, which have taken Western Europe over the past five hundred years. It makes easier to understand the past, the present and the future. Just as in collective drama, so this revolution started from a prelude, and then two acts have followed. The drama has introduced three factors, which determine the whole demographic evolution: a number of marriages, reproductiveness and mortality. During the prelude the proscenium was occupied by the first factor owing to creation of the „European model of marriage", constituted by a high average age of contraction of the first marriage and substantial proportion of unmarried women. Those two features hampered significantly birth possibilities in the era, when projected life duration was very restricted. The first act shows us a duel between life and deatfi, undergoing vicissitudes in dependence on countries and the decade, starting from the 18th century till 1930. At first mortality retreated, so in epidemic aspect as in endemic one. Infant mortality decrease resulted in improvement of projected life duration. That progress realized from the 18th century, and even more in the 19th century. Reproduction had its differentiated evolution until the last thirty years of the 19th century. A natural surplus became very significant in majority of countries. Only France differed in that respect. Still befor 1800 fertility in France diminished under the influence of the first wave, still restricted one, of „birth control" of peassant and handicraft types. When about 1880 the second wave, connected with industrialization, started in England, it reached the heart of hard-working Europe before 1914 and caused decrease in fertility, still lasting after the first world war. About 1930, demographic equilibrium was seriously disturbed in many countries. Just then an unexpected jump occured, causes of which deserve consideration, which caused a „baby boom" throughout 20 years. A new contraceptive offensive, which is created by trilogy: pill, abortion, sterilization, started about 1965. It caused a decrease in a replacement coefficient below an absolutely necessary level (2,10 children per woman) in all countries except Ireland. The decline was spectacular in many countries. And not without reason, people concerned with human future are frightened by the vision of Apocalypse. So, civilizations are mortal.
Five Hundred Years of Demographic Revolution in Western Europe